Electrocardiographic and echocardiographic evaluation of a large cohort of peri-pubertal soccer players during pre-participation screening. (29th August 2020) - Calò, Leonardo; Martino, Annamaria; Tranchita, Eliana; Sperandii, Fabio; Guerra, Emanuele; Quaranta, Federico; Parisi, Attilio; Nigro, Antonia; Sciarra, Luigi; Ruvo, Ermenegildo de; Casasco, Maurizio; Pigozzi, Fabio
Abstract: Background: The early diagnosis of cardiac abnormalities in young athletes may be helpful not only to identify subjects potentially at risk of sudden cardiac death but also to prevent stress-related cardiac dysfunction and cardiovascular events during the life of these subjects. The aim of our study was to investigate the prevalence of cardiac abnormalities in a population of young male soccer players undergoing pre-participation screening through electrocardiogram and trans-thoracic echocardiography. Methods: All consecutive male football players undergoing pre-participation screening comprehensive of medical history, physical examination, 12-lead electrocardiogram and trans-thoracic echocardiography at the FMSI Sport Medicine Institute in Rome between January 2008–March 2009 were enrolled in the study. Results: Overall, 2261 consecutive young athletes aged 12.4 ± 2.6 years were evaluated. Training-unrelated electrocardiogram abnormalities were observed in 65 (2.9%) athletes. Abnormal trans-thoracic echocardiography was observed in 102 athletes (4.5%), including two cases of hypertrophic cardiomyopathy, eight of mild left ventricular hypertrophy, six of mild left ventricular dilation and 17 of bicuspid aortic valve. An abnormal electrocardiogram was associated with anomalous trans-thoracic echocardiography in 11/65 (16.9%) cases. All athletes requiring sport disqualification were identified by electrocardiogram. Notably, among 2216 athletes with a normal electrocardiogram, 91 had abnormal trans-thoracic echocardiography, including six cases of left ventricular dilation and six of ventricular hypertrophy. Conclusions: In a wide population of peri-pubertal male athletes, evaluation of the electrocardiogram identified all cardiac diseases requiring sport disqualification. Trans-thoracic echocardiography alone allowed the identification of cardiac abnormalities potentially leading to cardiomyopathies or major cardiovascular events over time.